Fishing out microorganisms for bioremediation using metagenomics: Isolation and whole-genome sequencing of the metabolically versatile Rhodococcus erythropolis LP27217 strain from oil spill lake - Emilio D’Ugo; Arghya Mukherjee; Marco Resitano; Roberto Giuseppetti; Daniela Fortini; Bruna Matturro; Mattea Chirico; Maria Elena Pisanu; Matteo Tucci; Roberta Pozzi; Nicola Lovecchio; Owczarek Slawomir; et al. (Journal of Hazardous Materials, 2025)

Towards harmonization of metal(loid)s determination in conventional and compostable plastics: Comparison of acid digestion protocols in LDPE and PBAT/TPS blends - Stefano Carnati; Andrea Pozzi; Davide Spanu; Roberta Bettinetti; Luca Nizzetto; Gabriela Kalčíková; Ludovica Botta; Gilberto Binda (Chemosphere, 2024)

Heterogeneous mineralogical composition and fault behaviour: A systematic study in ternary fault rock compositions - Roberta Ruggieri; Giacomo Pozzi; Giuseppe Volpe; Francesca Bottazzi; Marco Brignoli; Anna Antonia Irene Corradi; Stefano Mantica; Lorenzo Osculati; Stefania Petroselli; Giorgio Volontè; Cristiano Collettini (Tectonophysics, 2024)

Selection of the optimal extraction protocol to investigate the interaction between trace elements and environmental plastic - Gilberto Binda; Stefano Carnati; Davide Spanu; Arianna Bellasi; Rachel Hurley; Roberta Bettinetti; Damiano Monticelli; Andrea Pozzi; Luca Nizzetto (Journal of Hazardous Materials, 2023)

Physicochemical and biological ageing processes of (micro)plastics in the environment: a multi-tiered study on polyethylene - Gilberto Binda; Giorgio Zanetti; Arianna Bellasi; Davide Spanu; Ginevra Boldrocchi; Roberta Bettinetti; Andrea Pozzi; Luca Nizzetto (Environmental Science and Pollution Research, 2023)
Pollution by plastic and microplastic impacts the environment globally. Knowledge on the ageing mechanisms of plastics in natural settings is needed to understand their environmental fate and their reactivity in the ecosystems. Accordingly, the study of ageing processes is gaining focus in the context of the environmental sciences. However, laboratory-based experimental research has typically assessed individual ageing processes, limiting environmental applicability. In this study, we propose a multi-tiered approach to study the environmental ageing of polyethylene plastic fragments focusing on the combined assessment of physical and biological processes in sequence. The ageing protocol included ultraviolet irradiation in air and in a range of water solutions, followed by a biofouling test. Changes in surface characteristics were assessed by Fourier transform infrared spectroscopy, scanning electron microscopy, and water contact angle. UV radiation both in air and water caused a significant increase in the density of oxidized groups (i.e., hydroxyl and carbonyl) on the plastic surface, whereby water solution chemistry influenced the process both by modulating surface oxidation and morphology. Biofouling, too, was a strong determinant of surface alterations, regardless of the prior irradiation treatments. All biofouled samples present (i) specific infrared bands of new surface functional groups (e.g., amides and polysaccharides), (ii) a further increase in hydroxyl and carbonyl groups, (iii) the diffuse presence of algal biofilm on the plastic surface, and (iv) a significant decrease in surface hydrophobicity. This suggests that biological-driven alterations are not affected by the level of physicochemical ageing and may represent, in real settings, the main driver of alteration of both weathered and pristine plastics. This work highlights the potentially pivotal role of biofouling as the main process of plastic ageing, providing useful technical insights for future experimental works. These results also confirm that a multi-tiered laboratory approach permits a realistic simulation of plastic environmental ageing in controlled conditions.

Sulphurous thermal water inhalation impacts respiratory metabolic parameters in heavy smokers - Cecilia Carubbi; Elena Masselli; Elisa Calabrò; Elisa Bonati; Carlotta Galeone; Roberta Andreoli; Matteo Goldoni; Massimo Corradi; Nicola Sverzellati; Giulia Pozzi; Antonio Banchini; Ugo Pastorino; et al. (International Journal of Biometeorology, 2019)

Differential cellular localization of Epstein–Barr virus and human cytomegalovirus in the colonic mucosa of patients with active or quiescent inflammatory bowel disease - Rachele Ciccocioppo; Francesca Racca; Luigia Scudeller; Antonio Piralla; Pietro Formagnana; Lodovica Pozzi; Elena Betti; Alessandro Vanoli; Roberta Riboni; Peter Kruzliak; Fausto Baldanti; Gino Roberto Corazza (Immunologic Research, 2016)

Distinct mechanisms contribute to immunity in the lantibiotic NAI ‐107 producer strain M icrobispora ATCC PTA ‐5024 - Roberta Pozzi; Murray Coles; Dirk Linke; Andreas Kulik; Mulugeta Nega; Wolfgang Wohlleben; Evi Stegmann (Environmental Microbiology, 2016)
The investigation of self‐resistance in antibiotic producers is important to understand the emergence of antibiotic resistance in pathogens and to improve antibiotic production. Lantibiotics are ribosomally synthesized antibiotics that mostly target peptidoglycan biosynthesis. The actinomycete M icrobispora ATCC PTA ‐5024 produces the lantibiotic NAI ‐107, which interferes with peptidoglycan biosynthesis by binding bactoprenol‐pyrophosphate‐coupled peptidoglycan precursors. In order to understand how M icrobispora counteracts the action of its own antibiotic, its peptidoglycan composition was analysed in detail. M icrobispora peptidoglycan consists of muropeptides with D ‐ A la and G ly in similar proportion at the fourth position of the peptide stems and alternative 3‐3 cross‐links besides the classical 4‐3 cross‐links. In addition, the NAI ‐107 biosynthetic gene cluster ( mlb ) was analysed for the expression of immunity proteins. We show that distinct immunity determinants are encoded in the mlb cluster: the ABC transporter MlbYZ acting cooperatively with the transmembrane protein MlbJ and the lipoprotein MlbQ . NMR structural analysis of MlbQ revealed a hydrophobic surface patch, which is proposed to bind the cognate lantibiotic. This study demonstrates that immunity in M icrobispora is not only based on one determinant but on the action of the distinct immunity proteins MlbQ , MlbYZ and MlbJ .

Long-Term Operation of an ASBBR Used to Treat Dairy Effluent: Effect of the Recirculation Rate on System Monitoring, Kinetics, and Key Microorganisms - Roberta S. S. Santana; Mayara S. Figueiredo; Eloisa G. Pozzi; Isabel K. Sakamoto; Júlio C. C. Balieiro; Mariza P. Melo; Rogers Ribeiro; Giovana Tommaso (Water, Air, & Soil Pollution, 2014)

Transcranial Direct Current Stimulation (tDCS) of the Cortical Motor Areas in Three Cases of Cerebellar Ataxia - Nicolò Gabriele Pozzi; Brigida Minafra; Roberta Zangaglia; Roberto De Marzi; Giorgio Sandrini; Alberto Priori; Claudio Pacchetti (The Cerebellum, 2014)

Upregulation of Tissue and Urinary Nicotinamide N-Methyltransferase in Bladder Cancer: Potential for the Development of a Urine-Based Diagnostic Test - Davide Sartini; Giovanni Muzzonigro; Giulio Milanese; Valentina Pozzi; Alexia Vici; Stefano Morganti; Valentina Rossi; Roberta Mazzucchelli; Rodolfo Montironi; Monica Emanuelli (Cell Biochemistry and Biophysics, 2013)